Studying the Efficacy of Psychodrama With the Hermeneutic Single Case Efficacy Design: Results From a Longitudinal Study - Gonzalez, António-José; Martins, Paulo; Lima, Margarida Pedroso de (Frontiers in Psychology, 2018)
Throughout the last decades, scientific and therapeutic communities have made common efforts to collect reliable information concerning the efficacy of psychotherapies. One of these initiatives has, recently, involved the psychodrama community and its desire to achieve progress in the validation of this therapy. Based on Robert Elliott’s Hermeneutic Single Case Efficacy Design, we followed five participants (three women, two men, aged 27–48 years) of a psychodrama group over the course of their therapeutic process, which ranged from 24 months to 5 years. For the single case study, we selected the participant who had the longest data collecting record, including one follow-up. Participants generally reported improvement in their personal therapeutic goals, decrease in symptoms and life problems, and some showed a marked increase in spontaneity levels. In the single case, these results are confirmed, and following decision criteria it is possible to assert that the participant improved in all the variables assessed and that therapy is the main cause of these changes. Furthermore, the participant frequently rated psychodrama sessions as being helpful and stated they had a transformational impact on his life. This research contributes toward validating psychodrama as an efficient therapeutic method, hopefully stimulating practitioners to integrate therapy and research—which, for years, were considered independent and incompatible—and to facilitate their use in a complementary way.